Análisis financieros: una herramienta clave para la toma de decisiones de gerencia. - Aguilar Guijarro, Clara Liseth; Marcillo Cedeño, Cristhian Arnaldo (My University, 2021)
Financial analyzes are considered a fundamental piece to be able to detect the situation, as well as the economic and financial performance of any organization, through which difficulties can be detected and then the necessary corrections can be made. The objective that has been raised through this study is to analyze what is the degree of relevance that is given to financial analysis as a key instrument in management decision-making, which is why a bibliographic study is carried out by means of theoretical bases of several authors. A financial analysis or study is based on the calculations of financial indicators, which are expressed by efficiency, solvency, performance, liquidity, indebtedness, and the profitability of the entity, financial analyzes are based on concrete amounts due to inflation the same amount that is provided by true, current, financial and accurate information. It can be concluded by stating that financial analyzes are both analytical and key management tools for the activities carried out by every organization, which determine the financial situations, which it is going through, thus allowing to recognize what the future it will have will be..
Los análisis financieros son considerados una pieza fundamental para poder detectar la situación, así como el desempeño tanto económico como el financiero que tiene toda organización, por medio del cual se podrán detectar las dificultades y luego poder realizar las correcciones necesarias. El objetivo que se ha planteado por medio de este estudio es el de analizar cuál es el grado de relevancia que se le da a los análisis financieros como un instrumento clave en la toma de decisiones de gerencia, es así que se realiza un estudio bibliográfico por medio de bases teóricas de varios autores. Un análisis o estudio financiero se llega a basar en el cálculo de los indicadores de las finanzas los mismos que son expresados por la eficiencia, solvencia, rendimiento, liquidez, endeudamiento, y la rentabilidad que posee la entidad, los análisis financieros se encuentran basados en cantidades concretas debido a la inflación la misma que se proporciona por la información veraz, actual, financiera y precisa. Se puede concluir expresando que los análisis financieros son herramientas tanto analíticas y gerenciales claves para las actividades que realiza toda organización las cuales determinan las situaciones financieras, por las que está pasando permitiendo así reconocer cual será el futuro que tendrá la misma.
Keywords: ANÁLISIS FINANCIERO; HERRAMIENTAS; INDICADORES FINANCIEROS